Wind speed as an independent variable to forecast the trap catch of the fruit fly (Bactrocera dorsalis) - VERGHESE, ABRAHAM; NAGARAJU, D K; MADHURA, H S; KAMALAJAYANTHI, P D; SREEDEVI, D K (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2001 - 02 at Bangalore to develop a weather based forcast Model for the Oriental fruit fly [Bactrocera dorsalis (Henden] a pest on mango(Mangifera indica L.) in India. Methyl eugenol (a parapheromone) is one of the components in its integrated pest management as well as in monitoring. The results showed that the wind speed and minimum temperature influenced the trap catches. The coefficient of detennination (R2 ) was stronger for wind speed than the minimum temperature. A forecasting model based on wind speed using polynomial equation was arrived at y =1.2779x3 +30.859x2 - 208.17x +455.55, R2= 0.7303; y=O.8557x4 - 26.221x3+294.38x2-1402.6x +2415.4, R2 =0.7585 and found best to predict fruit fly catches.